Revisiting Gerunds and Present Participles: A Structured Literature Review of English -ing Forms - Doni Hadi Irawan; Muhamad Alfi Khoiruman; Dewi Untari (LinguaEducare: Journal of English and Linguistic Studies, 2026)
The English -ing form has long challenged grammatical description because it appears in structures that function nominally, verbally, and adjectivally. In pedagogical grammar, this multifunctionality is commonly simplified through the distinction between gerunds and present participles. However, previous studies have shown that such a binary explanation often fails to account for the syntactic, semantic, and discourse-based variability of -ing constructions in authentic language use. Despite this, theoretical discussions of grammatical variation and pedagogical studies of learner difficulty have often remained disconnected. This study aimed to synthesize scholarship on gerunds and present participles, evaluate the analytical usefulness of the traditional distinction, and identify implications for grammar teaching in EFL/ESL contexts. The study employed a structured literature review design informed by systematic searching, screening, eligibility checking, and synthesis procedures. The data consisted of secondary sources, primarily peer-reviewed journal articles, supplemented by selected scholarly books and book chapters. Data were collected from Google Scholar, institutional repositories, and journal publisher platforms using keywords related to gerunds, present participles, -ing forms, and learner difficulties. The selected studies were analyzed through directed qualitative content analysis by coding and grouping findings into recurring categories such as syntactic function, semantic role, formal distribution, overlap, and pedagogical implications. The findings indicate that the distinction between gerunds and present participles remains analytically useful, but it should not be treated as a rigid binary category. Instead, -ing forms are better understood through distributional and contextual analysis. The review also shows that learners frequently struggle with these forms, suggesting the need for more contextualized, corpus-informed, and function-based grammar instruction.